Prevalence and Analysis of Risk Factors for RAI-Refractory Thyroid Cancer Patients: A 5-Year Retrospective Analysis from a Single Institution in Indonesia - Putri, Syifa Azizah; Monty Priosodewo Soemitro; Basuki Hidayat; Kharisma Perdani Kusumahstuti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Radioactive iodine (RAI) therapy is a cornerstone in the management of differentiated thyroid cancer (DTC). However, a subset of patients develops RAI-refractory disease, characterized by the inability to concentrate radioiodine, leading to limited treatment options and a poorer prognosis. This study aimed to investigate the prevalence and identify potential risk factors associated with RAI-refractory DTC in an Indonesian population. Methods: A retrospective analysis was conducted on patients diagnosed with DTC and treated with RAI at a single tertiary care center in Indonesia between 2019 and 2023. Data on demographics, clinical characteristics, tumor features, and treatment outcomes were collected. RAI-refractoriness was defined as the absence of iodine uptake on diagnostic whole-body scans after cumulative RAI activity of 600 mCi or more. Bivariate and multivariate analyses were performed to identify risk factors for RAI-refractoriness. Results: A total of 194 patients with DTC were included in the study. The prevalence of RAI-refractoriness was 90%. The median age at diagnosis was 55 years (range 18-82), and 72% were female. Papillary thyroid carcinoma was the most common histological subtype (92%). In bivariate analysis, older age at diagnosis (p=0.02), male gender (p=0.04), and the presence of distant metastases at diagnosis (p<0.001) were significantly associated with RAI-refractoriness. In multivariate analysis, only the presence of distant metastases remained an independent predictor of RAI-refractoriness (odds ratio 3.8, 95% confidence interval 1.5-9.2, p=0.003). Conclusion: RAI-refractoriness is a significant clinical challenge in the management of DTC, with a high prevalence observed in this Indonesian cohort. The presence of distant metastases at diagnosis emerged as a strong predictor of RAI-refractoriness. Further research is needed to elucidate the underlying mechanisms of RAI-refractoriness and develop novel therapeutic strategies for this patient population.